Utilizing Contextual Teaching Learning in Speaking Class - Kuwarso, Difia Ayu Audini; Karlina, Evi (Jurnal Ilmiah Wahana Pendidikan, 2024)
Learning how to communicate effectively through spoken language is a critical objective for all language students. To acquire English-speaking skills, the most appropriate approach must be chosen, and this study focused on Contextual Teaching Learning (CLT) since there are still many teachers who use unsuitable methods. This study employed the narrative technique to gain a better understanding of whether CTL is effective for teaching speaking, as well as its benefits. The participant of this study was the researcher herself who was an English teacher who taught speaking recently to grade two elementary students. The findings demonstrated that CTL is appropriate and effective for teaching speaking in English, which benefits students. CTL engages students by making them the center of the lesson. This allows students to make connections between their prior knowledge and the newly learned material. Additionally, CTL provides context for students to receive feedback on their prior knowledge, allowing them to change inaccurate prior knowledge into accurate prior knowledge.